2016
DOI: 10.1021/acs.chemrestox.6b00343
|View full text |Cite
|
Sign up to set email alerts
|

Thirdhand Smoke: New Evidence, Challenges, and Future Directions

Abstract: Thirdhand smoke (THS) is the contamination that persists after secondhand tobacco smoke has been emitted into air. It refers to the tobacco-related gases and particles that become embedded in materials, such as the carpet, walls, furniture, blankets, and toys. THS is not strictly smoke, but chemicals that adhere to surfaces from which they can be released back into the air, undergo chemical transformations and/or accumulate. Currently, the hazards of THS are not as well documented as the hazards of secondhand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
262
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 200 publications
(288 citation statements)
references
References 121 publications
(398 reference statements)
7
262
0
5
Order By: Relevance
“…The environmental signicance of this rebound phenomenon is that the positive effects of short-term ventilation to ush out a house or apartment are likely less than anticipated because many gas-phase species rapidly assume their preventilation mixing ratios aer the enhanced ventilation ceases. This is illustrated by the third-hand smoke phenomenon, [146][147][148] where the smell of cigarette smoke lingers long aer many full air exchanges. The lingering is due to the large pool of semi-volatile material sorbed to surface reservoirs.…”
Section: Multiphase Processes (A) the Nature Of Indoor Surfaces And Amentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental signicance of this rebound phenomenon is that the positive effects of short-term ventilation to ush out a house or apartment are likely less than anticipated because many gas-phase species rapidly assume their preventilation mixing ratios aer the enhanced ventilation ceases. This is illustrated by the third-hand smoke phenomenon, [146][147][148] where the smell of cigarette smoke lingers long aer many full air exchanges. The lingering is due to the large pool of semi-volatile material sorbed to surface reservoirs.…”
Section: Multiphase Processes (A) the Nature Of Indoor Surfaces And Amentioning
confidence: 99%
“…As an example, some third-hand smoke constituents [146][147][148]158 that sorb to indoor surfaces are sufficiently volatile that they affect the mass loading and composition of aerosol particles, via surface-to-gas-to-particle exchange. The dynamics of this process have been demonstrated in a university building impacted by nearby smokers.…”
Section: Multiphase Processes (A) the Nature Of Indoor Surfaces And Amentioning
confidence: 99%
“…The phrase "the four Rs" provides a working definition of THS: tobacco chemicals that remain, react, re-emit, and/ or are resuspended long after active smoking has ceased. 1,3,4 When tobacco is smoked, the particles in secondhand smoke settle on surfaces; this contamination is deeply absorbed into materials such as hair, clothing, carpeting, furniture and wallboard. The chemicals undergo an aging process after depositing on surfaces, which changes the chemical structure of the smoke pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Similar associations of cotinine concentrations with age (β < −0.10, p < 0.0001), demographic characteristics (e.g., income), and number of cigarettes smoked by caregiver (β > 0.07, p < 0.0001) were found regardless of cotinine detection method; however, cotinine associations with sex and race/ethnicity were only found to be significant in models using LC-MS/MS-derived cotinine. Conclusions: Utilizing LC-MS/MS-based cotinine, associations of cotinine with sex and race/ethnicity of child were revealed that were not detectable using ELISA-based cotinine, demonstrating the benefits of utilizing the more sensitive LC-MS/MS assay for cotinine measurement when detecting low levels of TSE in children.includes exposure from both secondhand smoke (SHS) and thirdhand smoke (THS), measurement needs to be reliable, highly sensitive and specific so that even low levels of THS exposure can be detected [1,7]. Nicotine is predominantly derived from combustible and noncombustible tobacco/nicotine products.…”
mentioning
confidence: 99%
“…includes exposure from both secondhand smoke (SHS) and thirdhand smoke (THS), measurement needs to be reliable, highly sensitive and specific so that even low levels of THS exposure can be detected [1,7]. Nicotine is predominantly derived from combustible and noncombustible tobacco/nicotine products.…”
mentioning
confidence: 99%